2011
DOI: 10.1042/bj20101386
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide synthase 4 and de novo production of ceramides with specific N-acyl chain lengths are involved in glucolipotoxicity-induced apoptosis of INS-1 β-cells

Abstract: Pancreatic β-cell apoptosis induced by palmitate requires high glucose concentrations. Ceramides have been suggested to be important mediators of glucolipotoxicity-induced β-cell apoptosis. In INS-1 β-cells, 0.4 mM palmitate with 5 mM glucose increased the levels of dihydrosphingosine and dihydroceramides, two lipid intermediates in the de novo biosynthesis of ceramides, without inducing apoptosis. Increasing glucose concentrations to 30 mM amplified palmitate-induced accumulation of dihydrosphingosine and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 60 publications
(77 reference statements)
9
106
2
1
Order By: Relevance
“…1E, to 112.7 Ϯ 11.2 from 209.3 Ϯ 31.6 pmol/mg protein, p ϭ 0.015) and islets (F, to 38.3 Ϯ 4.2 from 61.5 Ϯ 5.1 pmol/mg protein, p ϭ 0.0045) with palmitate treatment. Previous studies of INS-1 ␤-cells showed an increased content of the de novo Cer biosynthetic product dihydroceramide after 24 h of palmitate exposure (28). However, we did not observe this in either MIN6 cells (Fig.…”
Section: Comparative Lipidomic Analysis Of Min6 Cells and Pancreatic contrasting
confidence: 53%
See 1 more Smart Citation
“…1E, to 112.7 Ϯ 11.2 from 209.3 Ϯ 31.6 pmol/mg protein, p ϭ 0.015) and islets (F, to 38.3 Ϯ 4.2 from 61.5 Ϯ 5.1 pmol/mg protein, p ϭ 0.0045) with palmitate treatment. Previous studies of INS-1 ␤-cells showed an increased content of the de novo Cer biosynthetic product dihydroceramide after 24 h of palmitate exposure (28). However, we did not observe this in either MIN6 cells (Fig.…”
Section: Comparative Lipidomic Analysis Of Min6 Cells and Pancreatic contrasting
confidence: 53%
“…Moreover, when assessed directly, palmitate did not appear to promote misfolding of a reporter protein (27). An alternative, initially proposed by us (27) and now confirmed independently (28,29), postulates that palmitate slows protein trafficking out of the ER, which would, therefore, enhance ER stress because of lumenal protein overload. Our work further linked this trafficking defect to alterations in SL metabolism, although both the exact metabolite and the underlying mechanism remained obscure (30).…”
mentioning
confidence: 99%
“…Palm is a precursor of palmitoyl CoA [19], which is implicated in ceramide synthesis de novo. Accordingly, excessive Palm induced ceramide accumulation via promoting ceramide synthesis de novo and caused β cell impairment [20]. Interestingly, an in vivo animal study revealed that inhibition of NCDase activity was an underlying mechanism by which saturated fatty acid induced endogenous ceramide accumulation in rat skeletal muscle [21].…”
Section: Discussionmentioning
confidence: 99%
“…Our mass spectrometry and inhibitor analyses support this hypothesis. In addition, 1-deoxysphinganine increased the expression of CerS5, whereas b-cell lipotoxicity resulting from palmitate treatment stimulated the synthesis of CerS4 (31), suggesting that different lipids stimulate specific CerS isoforms. Collectively, the results suggest that some of the cytotoxic effects of 1-deoxysphinganine occur after its intracellular uptake and metabolism to 1-deoxy-dihydroceramide.…”
Section: -Deoxy-dihydroceramide Contributes To 1-deoxysphinganine-inmentioning
confidence: 99%